2005
DOI: 10.1021/jp0461652
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Activation of PtRu/C Catalysts for Methanol Oxidation

Abstract: Anodic treatment of PtRu/C catalysts in 0.5 M sulfuric acid at 1.3 V (vs RHE) for 0.5 h was found able to promote the activity for methanol oxidation by a few tenths to 5 times. This anodic activation effect was valid for samples domestically prepared under different conditions and that produced by Johnson-Matthey. On the basis of the changes of cyclic voltammetry during the anodic treatment, a model was proposed for the activation effect. According to the model, there are two categories of ruthenium oxides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 48 publications
2
59
0
Order By: Relevance
“…With increase in the CV cycles, the hydrogen desorption peaks increased significantly, which means exposure of Pt on the catalyst surface occurred. A large current density observed at high potential range (0.6-1.2 V) along the positive scan direction significantly decreased with increasing CV cycles, which might come from irreversible oxidation of Ru [43,44] and dissolution of Se [45]. A reduction peak observed between 0.5 and 0.8 V along the negative scan direction decreased with increasing CV cycles, which corresponds to the large decrease of the oxidation/dissolution peak of Ru/Se.…”
Section: Preparation and Characterisation Of Powder Catalystsmentioning
confidence: 90%
“…With increase in the CV cycles, the hydrogen desorption peaks increased significantly, which means exposure of Pt on the catalyst surface occurred. A large current density observed at high potential range (0.6-1.2 V) along the positive scan direction significantly decreased with increasing CV cycles, which might come from irreversible oxidation of Ru [43,44] and dissolution of Se [45]. A reduction peak observed between 0.5 and 0.8 V along the negative scan direction decreased with increasing CV cycles, which corresponds to the large decrease of the oxidation/dissolution peak of Ru/Se.…”
Section: Preparation and Characterisation Of Powder Catalystsmentioning
confidence: 90%
“…The current density from the irreversible Ru (hydrous) oxides decreased with increasing number of CV cycles, which means dissolution or formation of reversible Ru (hydrous) oxides. A lack of noticeable changes in the proton adsorption region (0*0.3 V along the positive scan direction) indicates that the irreversible Ru (hydrous) oxides were changed to the reversible Ru (hydrous) oxides during the CV tests [20]. In the heat treated catalysts, oxidation/reduction of the irreversible Ru (hydrous) oxides was also observed; however, a change in the current density corresponding to the increasing number of CV cycles was significantly suppressed.…”
Section: Resultsmentioning
confidence: 98%
“…It was shown that RuO 2 is a poor promoter of methanol electro-oxidation [14], and recent reports also showed that RuO x H y is more active than the metallic Ru [15][16][17][18][19]. On the other hand, Lu et al [20] divided Ru (hydrous) oxides (RuO 2 and RuO x H y ) into reversible and irreversible ones. They claimed that the reversible Ru (hydrous) oxide is beneficial for MOR, while the irreversible one is harmful.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of ruthenium oxides (RuO x or RuO x H y ) acting as co-catalysts has attracted recent interest and debate [32][33][34][35][36][37][38][39][40] Here we report the use of crystalline ruthenic acid nanosheets derived from H 0.2 RuO 2.1 ·xH 2 O as a co-catalyst for platinum towards CH 3 OH and CO electro-oxidation in an acidic environment.…”
Section: Introductionmentioning
confidence: 99%